Human mesenchymal stromal cells release functional mitochondria in extracellular vesicles - Thomas, Matthew A.; Fahey, Megan J.; Pugliese, Brenna R.; Irwin, Rebecca M.; Antonyak, Marc A.; Delco, Michelle L. (Frontiers in Bioengineering and Biotechnology, 2022)
Cartilage and other skeletal soft tissues heal poorly after injury, in part due to their lack of vascularity and low metabolic rate. No pharmacologic approaches have proven effective in preventing chronic degenerative disease after joint injury. Mesenchymal stromal cells (MSCs) have been investigated for their ability to treat pain associated with osteoarthritis (OA) and preserve articular cartilage. Limitations of MSCs include variability in cell phenotype, low engraftment and retention rates, and inconsistent clinical outcomes. Therefore, acellular biologic therapies such as extracellular vesicles (EVs) are currently being investigated. MSC-derived EVs have been found to replicate many of the therapeutic effects of their cells of origin, but the mechanisms driving this remain unclear. Recent evidence in non-orthopedic tissues suggests MSCs can rescue injured cells by donating mitochondria, restoring mitochondrial function in recipient cells, preserving cell viability, and promoting tissue repair. Our group hypothesized that MSCs package mitochondria for export into EVs, and that these so-called “mitoEVs” could provide a delivery strategy for cell-free mitochondria-targeted therapy. Therefore, the goals of this study were to: 1) characterize the vesicle fractions of the MSCs secretome with respect to mitochondrial cargoes, 2) determine if MSC-EVs contain functional mitochondria, and 3) determine if chondrocytes can take up MSC-derived mitoEVs. We isolated exosome, microvesicle, and vesicle-free fractions from MSC-conditioned media. Using a combination of dynamic light scattering and nanoparticle tracking, we determined that MSC-EV populations fall within the three size categories typically used to classify EVs (exosomes, microvesicles, apoptotic bodies). Fluorescent nanoparticle tracking, immunoblotting, and flow cytometry revealed that mitochondrial cargoes are abundant across all EV size populations, and mitoEVs are nearly ubiquitous among the largest EVs. Polarization staining indicated a subset of mitoEVs contain functional mitochondria. Finally, flow cytometry and fluorescent imaging confirmed uptake of mitoEVs by chondrocytes undergoing rotenone/antimycin-induced mitochondrial dysfunction. These data indicate that MSCs package intact, functional mitochondria into EVs, which can be transferred to chondrocytes in the absence of direct cell-cell interactions. This work suggests intercellular transfer of healthy MT to chondrocytes could represent a new, acellular approach to augment mitochondrial content and function in poorly-healing avascular skeletal soft tissues.